2015
DOI: 10.1371/journal.pone.0144082
|View full text |Cite
|
Sign up to set email alerts
|

Visual Benefits in Apparent Motion Displays: Automatically Driven Spatial and Temporal Anticipation Are Partially Dissociated

Abstract: Many behaviourally relevant sensory events such as motion stimuli and speech have an intrinsic spatio-temporal structure. This will engage intentional and most likely unintentional (automatic) prediction mechanisms enhancing the perception of upcoming stimuli in the event stream. Here we sought to probe the anticipatory processes that are automatically driven by rhythmic input streams in terms of their spatial and temporal components. To this end, we employed an apparent visual motion paradigm testing the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 53 publications
(99 reference statements)
5
19
0
Order By: Relevance
“…Additionally, the current results may have implications for attempts to entrain oscillatory activity through methods such as visual flicker (Ahrens et al, 2015;Capilla et al, 2011;de Graaf et al, 2013;Gulbinaite et al, 2017;Keitel et al, 2018a;Keitel et al, 2014;Mathewson et al, 2012;Notbohm and Herrmann, 2016;Spaak et al, 2014) and non-invasive transcranial brain stimulation (NTBS) (Helfrich et al, 2014;Romei et al, 2016;Thut et al, 2017;Veniero et al, 2017). It has recently been suggested that aligning external stimulation frequency with the endogenous peak alpha frequency may represent an optimal approach to effectively enhance/entrain alpha oscillations (Cecere et al, 2015;Gulbinaite et al, 2017;Romei et al, 2016;Thut et al, 2017;Vossen et al, 2015).…”
Section: Methodological and Applied Considerationsmentioning
confidence: 89%
“…Additionally, the current results may have implications for attempts to entrain oscillatory activity through methods such as visual flicker (Ahrens et al, 2015;Capilla et al, 2011;de Graaf et al, 2013;Gulbinaite et al, 2017;Keitel et al, 2018a;Keitel et al, 2014;Mathewson et al, 2012;Notbohm and Herrmann, 2016;Spaak et al, 2014) and non-invasive transcranial brain stimulation (NTBS) (Helfrich et al, 2014;Romei et al, 2016;Thut et al, 2017;Veniero et al, 2017). It has recently been suggested that aligning external stimulation frequency with the endogenous peak alpha frequency may represent an optimal approach to effectively enhance/entrain alpha oscillations (Cecere et al, 2015;Gulbinaite et al, 2017;Romei et al, 2016;Thut et al, 2017;Vossen et al, 2015).…”
Section: Methodological and Applied Considerationsmentioning
confidence: 89%
“…In terms of experimental paradigms, predictive symbolic cues are typically employed to engage endogenous attention, whilst transient and non-predictive sensory events, such as brief flashes, are used to test exogenous orienting (Petersen & Posner, 2012;Posner, 1980). Alternatively, visual flicker and apparent motion streams can exogenously drive attention (Ahrens, Veniero, Gross, Harvey, & Thut, 2015;Breska & Deouell, 2014;de Graaf et al, 2013;Rohenkohl, Coull, & Nobre, 2011). However, in the conventional design, tests for exogenous attention are typically employed in isolation, without controlling for endogenous attention (but see Berger et al, 2005;Ahrens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, visual flicker and apparent motion streams can exogenously drive attention (Ahrens, Veniero, Gross, Harvey, & Thut, 2015;Breska & Deouell, 2014;de Graaf et al, 2013;Rohenkohl, Coull, & Nobre, 2011). However, in the conventional design, tests for exogenous attention are typically employed in isolation, without controlling for endogenous attention (but see Berger et al, 2005;Ahrens et al, 2015). Consequently, participants may endogenously engage with the exogenous cues and adopt strategies to predict forthcoming events, by attempting to extract regularities based on the nature of events, even if this information is random and non-informative (Ahrens et al, 2015;Breska & Deouell, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a oddball detection task using auditory stimuli, both spatial and temporal orienting were found to benefit spatial processing performance (Lange, Krämer, & Röder, 2006). Although there is evidence of dissociations between the effects on performance of spatial and temporal orienting following exogenous cueing (Ahrens, Veniero, Gross, Harvey, & Thut, 2015;Jones, 2014), when attentional shifts are endogenously driven, the evidence points to similarities, and even interacting performance benefits, from spatial and temporal orienting. Rohenkohl, Gould, Pessoa, and Nobre (2014) reported that benefits to spatial discrimination performance are afforded by both spatial and temporal orienting, in addition to characterizing the interaction between these two types of orienting.…”
mentioning
confidence: 99%